Bob Spain's canoeing guide and favorite Texas paddling trails - Spain, Bob (River books (Series), 2018)
Premiere paddler and Texas Canoe Racing Hall of Famer Bob Spain presents a thorough and personal guide to all aspects of canoeing. He opens with a brief history of canoes and canoe making in North America followed by an illustrated how-to section on proper paddling technique and posture. Instructional photos and drawings by Spain?s paddling partner and wife, Joy Emshoff, help make your first-time paddling adventure less intimidating and more enjoyable. Readers will learn how to hold a paddle, perform basic strokes, and improve their technique as well as gain important information on the various types of canoes available. A handy checklist in the back of the book outlines important safety gear and essential equipment to pack in your canoe for day trips and overnight expeditions. Both newcomers to the sport and seasoned paddlers will find Spain?s detailed descriptions of his ten favorite inland and coastal Texas paddling trails entertaining and helpful. He provides useful logistical information?such as launch and take-out locations?GPS coordinates, available camping sites, and suggestions for nearby paddling trails. These trails offer paddlers a unique opportunity to explore the state and its varied wildlife while promoting the importance of preserving waterways. Spain concludes with a discussion on pressing conservation issues?water pollution, urban growth, habitat destruction, invasive species, and natural disasters?and the role ordinary people can have in protecting these natural resources for future generations. (Printed on waterproof paper).